Association between sleep disorder and anhedonia in adolescence with major depressive disorder: the mediating effect of stress - Xinxin Zhao; Hongzhe Ma; Ning Li; Wenjun Wu; Xinxu Ma; Xinxin Zhang; Wenming Liu; Lei Shang; Huaning Wang; Hailong Dong; Chen Li; Guangchao Zhao; et al. (BMC Psychiatry)
Abstract Background Major depressive disorder (MDD) is a highly prevalent mental disorder with devastating consequences that often first manifest during adolescence. Anhedonia has emerged as one of the most promising symptoms of adolescent MDD, which means a longer time to remission， fewer depression-free days, and also increased risk of suicide ideas or actions. Research has shown that at least two-thirds of depressed adolescents have significant sleep-onset or sleep-maintenance problems. However, the association between sleep disorder and anhedonia, and the potential mediators are less understood. Methods This is a cross-sectional study that includes 200 adolescents suffered from MDD between the ages of 12–17. We use Spearman’s test to explore the relationship among main variables. To evaluate the mediating effects of stress, we applied regression models and used bootstrap method to validate the significance of effects. Results Significant correlation exists among sleep disorder, stress, and anhedonia (P<0.05).The direct effect of sleep disorder on anhedonia was 0.214 (95% CI: 1.5235, 6.2073), while the total effect was 0.295 (95% CI: 2.9683, 7.6924). The indirect effect of sleep disorder on anhedonia mediated by stress was 0.081 (95% CI: 0.5842, 2.5268). Robustness of the regression analysis results has been verified by bootstrap test. Conclusions Our finding suggested a positive correlation between sleep disturbance and anhedonia in adMDD. Stress partially mediated the relationship between sleep disorder and anhedonia. Due to the deleterious effects of anhedonia on depressed adolescents, these findings provide impetus to investigate further the causal relationship between sleep problems and anhedonia. Trial registration ChiCTR2200060176(Registration Date: 21/05/2022).